SECURITY ISSUES OF ARCHAEOLOGICAL SITES AND THE EFFECT OF TECHNOLOGICAL DEVELOPMENTS IN THE CONTEXT OF EXAMPLES - Can Ozan Tuncer (İletişim Kuram ve Araştırma Dergisi)
Turkey is home to the most prominent ancient civilizations in history. It is crucial both for Turkey and world history that these lands, which have been the cradle of ancient civilizations, first-age civilizations, great empires, and states, should be preserved well. Apart from the traditional security needs of cultural areas, the study covers many different issues such as using new technologies in the security of these areas, increasing the attractiveness of the cultural regions as well as the safety of the environment, structure, and artefacts and visitors. The primary goal of this research was to identify the security and safety risks of three major archaeological sites. To that end, an observational study was conducted at the archaeological sites Mount Nemrut, the Ancient City of Perre and Göbeklitepe. Analysis of field notes suggested that risks that these three major archaeological sites face could be summarised as institutional and structural risks, natural risks and human activity-related risks. Research implications are discussed in the paper.